Políticas públicas de acesso à educação infantil no município de Campo Largo - PR (2003 – 2016) - Borges, Daniele Sant´Ana (2017)
The present dissertation has as object the “Public Policies of access to Childhood Education in the city of Campo Largo from 2003 to 2016”. This topic has been gaining space in researches and debates due to the campaigns in favor of the effectiveness of Childhood Education as set on relevant legislation, namely at PNE – Law 13,0005 from 2014, in its goal 1. The issue of this object was thus formulated: given the social struggles and the policies that express them, what are the policies of access to Childhood Education in the city of Campo Largo/PR? The general goal is to study the policies of access to Childhood Education in the city of Campo Largo, considering children between 0 and 5 years old, a historical, cultural and rights subject. The specific objectives are the following: to study how the conquest in favor the Childhood Education occurred on modern times and in Brazil, get to know the existing literature about this subject, taking as source of data the Digital Library and CAPES Library and investigate the policies of access to Childhood Education in the city of Campo Largo. Methodologically this dissertation has the presupposition that the real fact reveals itself and hides itself, and to get to know in depth the phenomena of reality it‟s necessary to go beyond the appearance in order to grasp its essence. Kosik is considered, and his contribution formulated in the literary work “Concrete Dialectics”. In this literary work, split in four chapters, Kosik begins with a reflection that reality does not immediately present itself to the man and its necessary to do a detour to grasp the essence of the phenomenon in order to overcome its phenomenic vision. This is a documentary research and it counts on the study of the Federal Constitution from 1998, the Law of Guidelines and Education Basis number 9,394/96 and the documents of the Municipal Secretary of Education of Campo Largo (normative instructions: nº 01/2005, nº 01/2006, nº 01/2007, nº 02/2007, nº 04/2010, nº 03/2012, nº 05/2013, nº 05/2014, nº 06/2015 and nº 02/2016), besides the study of IPARDES data about the city of Campo Largo. It was analyzed the municipal policies of access as a result of the Normative Instruction nº 02/2016, that makes the public call for the selection of students according to the number of vacancies available. In this case, taking a sample, it was analyzed 399 registers from five institutions (A, B, C D, and E) from Campo Largo. In Campo Largo the number of families that got a vacancy (42%) is under the number of those who didn‟t get any vacancy (58%). The largest number of vacancies was allocated to the Nursery Class II (54%), as well as the greater demand of the families was vacant in this class (45%). The greater demand for vacancies is located in the downtown area of the city (66%). Only fifteen families managed to get a vacancy on Childhood Education through the Bolsa Família Program. Mostly families that managed to get a vacancy in the institutions are composed for three family members (nuclear family). Both the per capita income of families that got vacancy and those that did not get a vacancy in the institutions is between R$ 1,000.00 and R$ 2,000.00. Still regarding the city of Campo Largo, there are a large number of children in the repressed demand, taking the last three year there is a number of 2,505 enrollees waiting for a vacancy. From the referred data, it is concluded that the policy of Childhood Education in the municipality is incipient. The argument for the non-attendance is a “reservation of the possible”, that means there is no greater offer because the public policy for Childhood Education does not universalize in the city of Campo Largo, and other values arise.